Liberdade, progresso e revolução: concepções estéticas, culturais e historiográficas na obra Os Miseráveis (1862), de Victor Hugo - Santos, Fernando Cesar dos (2017)
This paper aims to understand how Victor Hugo's creation `The Miserables` (1862) plays an important role in France’s discussion about the concepts of freedom, progress and revolution against the political and social life events during the nineteenth century, causing a resonance throughout Europe at the time of its publication. How the epic has enormous catalyzing yearning power aimed at the transformation of this unjust reality surrounded by misery on all sides.